Assessment of perioperative antibiotic prophylaxis for gynecological surgeries at an academic hospital in Brazil (Research, Society and Development, 2021)
The aim of this study was to assess the adequacy of physicians' practice patterns regarding the use of perioperative antibiotic prophylaxis for gynecological surgeries in an academic hospital specialized in gynecology located at Rio de Janeiro city, Brazil. This is a retrospective study assessing all gynecological surgeries performed over one year. Appropriateness of antibiotic prophylaxis was determined according to criteria adapted from evidence-based guidelines. Clinical practice regarding the use of perioperative antibiotic prophylaxis was considered appropriate for 58.4% of 416 surgeries. The non-indicated use of antimicrobial prophylaxis was the main factor determining the low percentage of overall adequacy. Three variables were independently associated with inappropriate administration of perioperative antibiotics: patients age, breast surgeries and longer procedures. Antibiotic prophylaxis compliance to published recommendations is low. Women undergoing gynecological surgery are exposed to unnecessary risks associated to non-indicated use of antibiotic prophylaxis. Strategies aimed to improve compliance to evidence-based guidelines are necessary.